The effects of the catch-up mechanism on the structural transformation of Sub-Saharan Africa - John Ssozi; Edward Bbaale (Economies, 2019)
Structural transformation is one of the processes of productivity growth urgently needed in Sub-Saharan Africa (SSA). This study uses the catch-up mechanism to analyze how international contacts and domestic absorptive capacity constraints are shaping the pattern of structural transformation in SSA. Using a two-step Generalized Method of Moments on 2000-2015 data for 29 SSA countries, the paper finds that SSA is undergoing a non-classical structural transformation led by the service sector instead of manufacturing. Import penetration, a key variable of international contact, has negative coefficients for both the agricultural and manufacturing shares of gross domestic product (GDP) but is positively associated with both the services shares of employment and GDP. A test of Kaldor's third law finds that if growth in employment outside manufacturing is in services, it can also increase economy-wide productivity. Hence, it is the international constraints, such as import penetration and foreign direct investment, that are making the structural transformation of SSA non-classical. Services that involve transfer of skills and technology, such as international tourism and information and communications technology services exports, provide opportunities for structural change and productivity growth.
Keywords: F43; F63; O14; O55; 330; absorptive capacity; foreign direct investment; import penetration; structural transformation